Hubungan Antara Asupan Imunonutrisi dengan Status Imunitas Pascapandemi COVID-19 - Anisa Maulidia; dian isti anggraini; sutarto (Medula, 2023)
The COVID-19 pandemic was announce by World Health Organization on March 11, 2020. The disease first appeared in Wuhan, China, and continued to spread to various countries around the world starting in December 2019. To reduce the spread of COVID-19, the Indonesian government implemented the Restriction of Community Activities (PPKM), which had an impact on various aspects of life, including health and the economy. After the reduction in morbidity of COVID-19, Indonesian President officially lifted the PPKM status on December 30, 2022. The government and all aspect work together to improve the post-pandemic situation. Until now, no drug has been found that can specifically cure COVID-19. This infection is the same as other viral infections, which have a self-limiting nature with the speed of recovery being influenced by the individual's immune status. Immune status is a condition of the immune system that protects a person's body from exposure to foreign objects. Factors that can affect the immunity status are age, intake of immunonutrition, hormones, and exposure to infection. Immunonutrition consists of certain nutrients that can help the immune system. This article is a literature review compiled to determine the relationship between immunonutrition intake with immunity status post-COVID-19 pandemic. The literature sources used in this article use national and international scientific articles that have been published in 2013–2022. There’re many impact of COVID-19 pandemic such as economic decrease that decrease purchasing power, including in the purchase of food. That’s all can cause the decreasing of immunity status.